Exploring the Mechanical Properties of Bioprinted Multi-Layered Polyvinyl Alcohol Cryogel for Vascular Applications - Argyro Panieraki; Nasim Mahmoodi; Carl Anthony; Rosemary J. Dyson; Lauren E. J. Thomas-Seale (Journal of Manufacturing and Materials Processing, 2025)
Polyvinyl alcohol cryogels (PVA-C) are promising materials for vascular tissue engineering due to their biocompatibility, hydrophilicity, and tuneable mechanical properties. This study investigates the mechanical performance of multi-layered PVA-C constructs fabricated via sub-zero extrusion-based three-dimensional (3D) bioprinting. Samples with two, four, and six alternating layers were evaluated to assess the effect of layered architecture on elastic and viscoelastic behaviour. Uniaxial tensile testing revealed that increasing the number of layers led to a moderate reduction in stiffness; for instance, at 20% strain, six-layered constructs showed a significantly lower (p < 0.05) Young’s modulus (36.7 ± 2.5 kPa) compared to two-layered ones (47.3 ± 3.1 kPa). Stress–strain curves exhibited nonlinear characteristics, better captured by quadratic (as opposed to linear) fitting, within the tested strain range (≤40%). Dynamic mechanical analysis demonstrated a frequency-independent storage modulus (E′) across 1–10 Hz, with subtle variations in viscoelastic response linked to the number of layers. Visual inspection confirmed improved print fidelity and hydration retention in thicker constructs. These findings demonstrate that a multi-layered design influences the mechanical profile of PVA-C and suggests potential for functionally graded design strategies to enhance compliance matching and mimic the biomechanics of native vessels in small-diameter vascular grafts.